Vitamin D Deficiency and Its Determinants in Adults: A Sample from Community-Based Settings in the United Arab Emirates - Wegdan Bani-issa; Kamal Eldeirawi; Sondos Harfil; Randa Fakhry (International Journal of Endocrinology)
Background. Vitamin D deficiency (VDD) is a public health concern in adults worldwide. This study aims to explore the extent of VDD and its associated factors among adults in the United Arab Emirates (UAE). Subjects and Methods. Quantitative, cross-sectional research was used to assess VDD and its associated factors in 216 adults recruited from randomly selected community-based healthcare settings over a six-month period. Recent values of vitamin D and glycated hemoglobin (HbA1c) were abstracted from medical records, followed by interviews with participants to obtain information on factors related to VDD and other covariates and to measure their heights and weights. Results. A total of 74% of participants demonstrated VDD (vitamin D serum level≤30 nmol/L). Emirati participants had higher odds of having VDD compared to non-Emiratis (OR: 2.95; 95% CI: 1.58–5.52), with also significantly increased odds of the condition appearing in older, less educated, and employed adults. Diabetes type 2 (HbA1c≥6.5%), depression, and obesity were significantly associated with an increased likelihood of VDD after accounting for other covariates. Conclusion. VDD is a significant problem for UAE adults and requires attention by public health policy makers. Diabetes, obesity, and depression need to be considered when screening for vitamin D.